Molecular determinants of ligand binding at the human histamine H(1) receptor: Site-directed mutagenesis results analyzed with ligand docking and molecular dynamics studies at H(1) homology and crystal structure models - Cordova-Sintjago, Tania C. (2012)
The human histamine H(1) G-protein coupled receptor (GPCR) is an important drug target for inflammatory, sleep, and other neuropsychiatric disorders. To delineate molecular determinants for ligand binding for drug discovery purposes, human H(1) receptor models were built by homology to the crystal structure of the human β(2) adrenoceptor (β(2)AR) and from the recently reported crystal structure of the human H(1) receptor complex with doxepin at 3.1 Å (PDB code 3RZE). Ligand affinity of histamine and the H(1) antagonists mepyramine and (2S, 4R)-(–)-trans-4-phenyl-2-N, N-dimethylaminotetralin (PAT) at wild type and point-mutated (D3.32A, Y3.33A, W4.56A, F5.47A, W6.48A, Y6.51A, F6.52A, F6.55A, Y7.43A) human H(1) receptors were determined experimentally and results analyzed by ligand docking and molecular dynamic studies at WT and point-mutated H(1) receptor models. Differences in ligand binding affinities correlated to differences in ligand binding modes at models built according to homology or crystal structure, indicating, both models are accurate templates for predicting ligand affinity for H(1) drug design.